2016
DOI: 10.1007/s10096-016-2651-7
|View full text |Cite
|
Sign up to set email alerts
|

Community-associated Staphylococcus aureus pneumonia among Greek children: epidemiology, molecular characteristics, treatment, and outcome

Abstract: Staphylococcus aureus is an infrequent cause of community-associated (CA-SA) pneumonia in children. The aim of this study was to evaluate the clinical, epidemiological, microbiological, and molecular characteristics of CA-SA pneumonia among children hospitalized in two large tertiary care referral centers during an 8-year period. Cases of CA-SA pneumonia admitted between 2007 and 2014 were retrospectively examined through medical record review. Molecular investigation was performed for available strains; mecA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…We found increased resistance for clindamycin (18%) but low for STX (4.6%), however 38% and 12.5% of MRSA isolates were resistant to clindamycin and STX, respectively. Our results are similar for clindamycin but much higher for STX compared with previous studies in Greek hospitals [ 12 , 18 , 19 ]. The high resistance to clindamycin limits its use for SSTI but STX may still be an option.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found increased resistance for clindamycin (18%) but low for STX (4.6%), however 38% and 12.5% of MRSA isolates were resistant to clindamycin and STX, respectively. Our results are similar for clindamycin but much higher for STX compared with previous studies in Greek hospitals [ 12 , 18 , 19 ]. The high resistance to clindamycin limits its use for SSTI but STX may still be an option.…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows high resistance of S. aureus strains to erythromycin (34.4%), much higher for MRSA (60%), making macrolides an unsuitable first-line choice for treatment of skin infections. Similar (31.7%) [ 18 ] or higher (49%) [ 19 ] rates of resistance to macrolides have been reported from other studies performed in Greece. Clindamycin is a bacteriostatic agent that is favored in the setting of staphylococcal skin infection due to its excellent skin penetration [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…This clone was also reported from other types of infections including fatal pneumonia and bloodstream infections [14,61,77,79]. In the study by Doudoulakakis et al, the authors reported that MRSA-ST80 PVL+ strains accounted for 95% of CA-MRSA pneumonia cases [14]. Nikolaras et al showed that 8% of MRSA strains isolated from bloodstream infections were assigned to MRSA-ST80 clone [77].…”
Section: Virulence Of Mrsa-st80mentioning
confidence: 76%
“…Epidemiological studies of MRSA-ST80 PVL+ have revealed that these strains are primarily associated with recurrent, chronic, or particularly severe SSTIs, such as furuncles and abscesses [114]. This clone was also reported from other types of infections including fatal pneumonia and bloodstream infections [14,61,77,79]. In the study by Doudoulakakis et al, the authors reported that MRSA-ST80 PVL+ strains accounted for 95% of CA-MRSA pneumonia cases [14].…”
Section: Virulence Of Mrsa-st80mentioning
confidence: 97%
“…In contrast to North America, CA-MRSA in Europe is characterized by bigger clonal heterogeneity. The predominant European clone is ST80-IV ( Figure 1 ), resistant to kanamycin/amikacin and fusidic acid [ 20 21 ], strongly associated with skin and soft tissue infections, rarely found among asymptomatic carriers. ST80 was first reported in 1993, but was relatively rare until the late 1990s [ 22 ].…”
Section: The Main Clones Of Ca-mrsa In the Worldmentioning
confidence: 99%